Electrochemical deposition and characterization of Ni-Mo alloy powders - M.G. Pavlović; B.M. Jović; V.D. Jović; U. Lačnjevac; V.M. Maksimović (Processing and Application of Ceramics, 2007)
Electrodeposition of Ni-Mo alloy powders from ammonium sulfate and ammonium chloride containing electrolytes of different Ni/Mo ions concentration ratios was investigated by polarization measurements. The morphology, chemical composition and phase composition of electrodeposited Ni-Mo alloy powders were investigated using DSC, TGA, SEM, EDS and XRD analysis. EDS results showed that powder composition depends on Ni/Mo ions concentration ratio, as well as on the position where the EDS analysis was performed. As-deposited alloy powders were nanocrystalline showing no XRD peaks with undefined morphology (SEM). After recrystallization for 2 h in N2 atmosphere at 600°C the presence of NiMoO4 phase was identified in the powder electrodeposited from chloride electrolyte at the Ni/Mo ions concentration ratio 1/3, with well defined crystalline powder particles.